ZERO ORDER AND AREA UNDER CURVE SPECTROPHOTOMETRIC METHODS FOR DETERMINATION OF AMOXICILLIN TRIHYDRATE IN PHARMACEUTICAL FORMULATION. - Mali, Audumbar Digambar (Innovare Journal of Sciences, 2016)
Objective: - A simple, accurate, precise and specific zero order and area under curve spectrophotometric methods has been developed for determination of Amoxicillin Trihydrate in its tablet dosage form by using methanol as a solvent. Â Â Methods: - (1) Derivative Spectrophotometric Methods: - The amplitudes in the zero order derivative of the resultant spectra at 229 nm was selected to find out Amoxicillin Trihydrate in its tablet dosage form by using methanol as a solvent. (2) Area under curve (Area calculation): -The proposed area under curve method involves measurement of area at selected wavelength ranges. Two wavelength ranges were selected 224-232 nm for estimation of Amoxicillin Trihydrate. Result & Discussion: -The linearity was found to be 5-25 Î¼g/ml for Amoxicillin Trihydrate. The mean % recoveries were found to be 100.33% and 99.42% of zero order derivative and area under curve method of Amoxicillin Trihydrate. For Repeatability, Intraday precision, Interday precision, % RSD were found to be 0.0036, 0.0028 and 0.5987, 0.4188 for zero order and 0.0019, 0.0031 and 1.6357, 1.7159 for area under curve method respectively. Limit of Detection and Limit of Quantitation were found to be 0.9142Î¼g/ml and 2.8128Î¼g/ml for zero order and 0.5798Î¼g/ml and 1.3153Î¼g/ml for area under curve method respectively. Assay results of market formulation were found to be 100.84% for zero order and 99.65% area under curve method respectively. The proposed method has been validated as per ICH guidelines and successfully applied to the estimation of Amoxicillin Trihydrate in its Tablet dosage form. Conclusion: - The developed methods can be concluded as accurate, sensitive and precise and can be easily applied to the pharmaceutical formulation.